Effectiveness of Foot Massage and Mitchell’s Relaxation Technique on Physiological and Psychological Parameters of Patients Undergoing Elective Angioplasty. - ., Shilpa; Sheeja, C. V.; Assuma Beevi, T. M. (International Journal of Nursing Research, 2023)
Aim: The aim of the study is to evaluate the effectiveness of foot massage and Mitchell’s relaxation technique on physiological and psychological outcome of patients undergoing elective angioplasty. Background: The physiological parameters of patients will be altered due to stress. Use of alternative therapies is needed to improve health and considered as therapeutic perquisites. Foot massage and Mitchell’s relaxation technique would reduce stress, blood pressure (BP), heart rate (HR), and respiratory rate and have certain health benefits. Methods: Quasi-experimental study with two group pre-test and post-test design was adopted with purposive sampling on 30 study participants who have fulfilled the inclusion criteria and randomly allotted into two groups. Group 1 for foot massage and Group 2 for Mitchell’s relaxation technique for 3 days at morning 7 AM and evening 7 PM. Socio-demographic and clinical profile datasheet and stress rating scale were used to collect the data. After giving six interventions, on 3rd -day post-test was done. Results: Both Mitchell’s relaxation technique and foot massage were effective in lowering physiological and psychological parameters. HR, BP, and stress level of patients who had massage and BP and stress level for those had Mitchell’s relaxation were statistically significant at 0.05 levels (P < 0.05). Age of the patient was significantly associated with HR. Exercise and personal habits had a significant association with pre-test stress score at 0.05 levels (P < 0.05). Conclusion: Foot massage is found to be more effective in reducing BP, HR, and stress level than Mitchell’s relaxation technique in patients undergoing elective angioplasty. As a regular nursing intervention, these therapies can be incorporated.